Cartografia Enterprise : RC Auto Scaler / Mohd Azlan Isa...[et.al] - Isa, Mohd Azlan; Azmi, Azmul Munir; Mat Nor, Mohd Riduan; Md Radzi, Najwa Husna; Mohd Yusof, Nurizety (Faculty of Plantation and Agrotechnology, 2016)
First off all we name our company as Cartografia Enterprise. The establishment of our company as the Cartografia Enterprise is in the 5 February 2016. Our company is based on partnership. The partnership agreement has been formed 5 October 2015 at the Bukit Katil, Melaka. This agreement is between our shareholders that have been list down. This company is leads by our General Manager name Muhammad Azlan Bin Isa and helped by five others sectional managers consists of Administration Manager, Operational Manager, Marketing Manager, Financial Manager and Asisstant Financial Manager. The person that holds that position is Nurizety Binti Mohd Yusof as Administration Manager, Najwa Husna Binti Md Radzi as Operational Manager, Khairul Ilman Bin Ab Karim as Marketing Manager, Azmul Munir Bin Azmi as Financial Manager and lastly Mohd Riduan Bin Mat Nor as the Assistant Financial Manager. We are located our company at Lot 1838 Mukim Bukit Katil Ayer Keroh, 75450 Melaka, 75450 Melaka, Malaysia. Each of the manager have their own tasks and responsibilities for this company that have they fulfilled. Based on the cooperation between all shareholders, we want to make that our business run smoothly and at the same time achieve the objective, mission and vision. This company have 10 employees that include General Manager, Administration Manager, Operational Manager, Marketing Manager, Financial Manager, and Assistant Financial Manager, 2 General Workers, 2 clerk. Our target group is middle man as contractor, developer, trader, agent, and civil engineer or direct sell to user. For the information, our sales per year is about RM 3 000 000.00. Cartografia Enterprise try to compete with two company that well establishment which is CRYSTAL SDN BHD and LAU&TAN TRADING. We found that this company have a few weakness which is these company have higher overhead cost, higher price that have been charged due to the quality of the product and service, and sometimes they are maybe because of the rush to delivery. Basically, the process involve handling of raw materials, put on body part, put on GPS and camera. In the other hand, the business is operating 5 days a week starting at 8.00 P.M. until 5.00 P.M. we predict our company will increase our product sale 9% by second year and another 13% from for the third year.